Unlocking tumor barrier: annexin A2-mediated transcytosis boosts drug delivery in pancreatic and breast tumors - Yanyan Liu; Qikai Wang; Zhenhan Feng; Mengmeng Qin; Zhenyu Zhang; Jinhong Jiang; Tongxiang Ren; Xiangsheng Liu; C. Jeffrey Brinker; Yuliang Zhao; Huan Meng (Nature Communications)
Abstract The efficacy of many cancer nanocarriers has traditionally been attributed to enlarged tumor vasculature fenestrations, giving rise to the concept of the enhanced permeability and retention (EPR) effect. However, emerging evidence suggests that active biological processes, such as transcytosis, may play a central (and sometimes dominant) role in nanoparticle transport across tumor vasculature. In this study, we develop lipid-coated mesoporous silica nanoparticles (LC-MSNP) as a model platform to investigate the contribution of surface-bound proteins to transcytosis-mediated tumor delivery. Through comparative analysis, we identify Annexin A2 (A2) as a key endogenous protein that facilitates this process. Pre-coating LC-MSNP with A2 significantly enhances the delivery of irinotecan and doxorubicin to breast and pancreatic tumors in vivo. This strategy is successfully extended to both an in-house liposome formulation and a commercial doxorubicin liposome, leading to improved therapeutic efficacy, including long-term survival in a subset of treated mice. Mechanistic studies reveal that this enhancement is governed by a specific nanosurface-A2-α5β1 integrin interaction. In both murine and patient-derived xenograft models, therapeutic benefit correlates with α5β1 integrin expression on tumor vasculature. These findings establish a mechanistic basis for protein-mediated transcytosis and provide a translational strategy to improve the performance of clinically approved nanomedicines.